Contribution of Migrant Workers in Increasing Remittances and Accelerating the SDGs : A Country Without Unemployment - Yougie Alhabsy Barnadi; Eny Haryati; Dian Ferriswara (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
This study aims to describe and analyze: The Contribution of Migrant Workers in Increasing Money Remittances and Achieving the SDGs. The research is a qualitative descriptive analysis. The data analysis technique uses the technique developed by McNabb (2002), namely Grouping the data according to key constructs, Identifying bases for interpretation, Developing generalizations from the data, Testing Alternative interpretations and Forming and/or refining generalizable theory from case study. The results of the study show that migrant workers play an important role in the world economy, especially in developed countries as migration destination countries and contribute to the growth of the economy in their home countries, one of which is through remittances sent to their home countries. Indonesia is one of the countries that still sends migrant workers, where remittances from migrant workers are seen as one of the main sources of foreign exchange after petroleum. Migrant workers contribute to reducing the unemployment rate in Indonesia by: Increasing household income. Helping families left behind not work for a while. Increase family access to capital and credit for entrepreneurship. Encouraging a decrease in child employment rates Helping economic development in the region of origin. Encourage political and social change. The use of remittances for productive activities is expected to increase investment in recipient countries. Remittances encourage improvements made by households in daily consumption, expenditure on education, health, and other expenses, so that it will affect economic growth. Remittances increase household incomes and are therefore a strong anti-poverty force in developing countries. Not only that, migrant workers who return to their home countries (return migrants) also contribute to the economic and social conditions of their home countries. Remittances can contribute directly and indirectly to several SDGs. Remittances' contribution to the SDGs: SDG 1: Reduce poverty, SDG 8: Decent work and economic growth SDG 10.c: Reduce the cost of migrant remittance transactions.